Answer:
Explanation:
Simplifying
16 = -12 + -7x
Solving
16 = -12 + -7x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '7x' to each side of the equation.
16 + 7x = -12 + -7x + 7x
Combine like terms: -7x + 7x = 0
16 + 7x = -12 + 0
16 + 7x = -12
Add '-16' to each side of the equation.
16 + -16 + 7x = -12 + -16
Combine like terms: 16 + -16 = 0
0 + 7x = -12 + -16
7x = -12 + -16
Combine like terms: -12 + -16 = -28
7x = -28
Divide each side by '7'.
x = -4
Simplifying
x = -4